Perancangan Sistem Pengawasan Kinerja Untuk Menunjang Pencapaian Perbaikan Berkesinambungan Program Studi - Syarif, Adi Chandra (TEMATIKA, Journal of Informatics and Information Systems, 2018)
Universities have the autonomy to manage themselves which regulates the planning, supervision, monitoring and evaluation systems to achieve the goals of higher education. One standard set in higher education is the application of information technology in the higher education governance system. In providing higher education sevices, University of Atma Jaya Makassar has utilized the application of information and communication technology infrastructure through the development of an Academic Information System (SIAMIK) and other supporting systems. The development of the lecture process management system (STKP) at the Faculty of Information Technology, University of Atma Jaya Makassar shows that the development has been able to integrate the supervisory function in the implementation of the lecture process by introducing the value of transparency and accountability. The STKP can provide convenience in evaluating the performance of study programs in the ongoing lecture process. The main objective of this research is to develop a system of supervision and integrated information services. With the information service study program can help universities, especially the information technology faculty in improving performance in the lecture process that is useful for lecturers, academic supervisors, study program chairmen and deans of the Faculty.Keywords: Academic Spervision System, Information Service.